Supporting Globally Distributed PBL Teams Using A Rich ICT Environment: How Do Participants Use Different Mediation Tools? - Cheng, Chew Swee; Beaumont, Chris; Poh, Seah Chong; Westhead, Gary (Proceedings of the International Conference on Networked Learning, 2004)
In the 21st century it is becoming increasingly common to work and learn in teams that are globally distributed. Such teams rely heavily on ICT to facilitate effective communication. There is a wide variety of communication tools and technologies to choose from and it is by no means obvious which tools should be used, and whether synergy exists when a communication environment is provided which includes a rich set of tools and media. This paper reports and analyses the use of communication tools by students in a distributed Problem-based Learning (dPBL) environment. The PBL teams consisted of four students from Singapore and four from the UK. Teams had a rich set of synchronous and asynchronous communication tools available to them, including ISDN videoconference, WebCam Video/Audio, Microsoft NetMeeting® Chat, Asynchronous drop box and threaded discussion Forum. This ethnographic study showed that semantic discussion threads included the use of all tools and enabled students to effectively co-construct meaning (and understanding). Students were able to deploy the use of different tools effectively to achieve the learning outcomes intended for various stages in the PBL cycle, with both asynchronous and synchronous media being considered of high importance.